Fiscal Rules in Times of Crisis - Bandaogo, Mahama Samir (World Bank, Washington, DC, 2020)
As governments around the world struggle to piece together the most effective fiscal response to counter the economic and social impact of the COVID-19 outbreak, some are facing constraints imposed by fiscal rules enacted in the past to ensure fiscal discipline. The outbreak has revealedthe weaknesses and inappropriateness of many existing fiscal rules, and authorities should take the opportunity to strengthen their fiscal rules by adopting features that make them more flexible, operational, and enforceable. Research shows that the de facto strength and credibility of the fiscal rule is what matters for fiscal discipline, not the mere de jure existence of one. As important as it is that fiscal rules include contingencies to accommodate large and effective fiscal responses to severe and unprecedented crises, it is also as important that fiscal rules provide clear guidance for building up savings in times of positive shocks.